(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The incorporation of software technologies into post-primary education has become one of the key approaches towards the development of scientific literacy and student engagement. This paper will discuss the ways in which digital science education: simulation software, virtual laboratories, and interactive learning platforms can change the approach to teaching science via inquiry-based learning and critical thinking. The studies explore the effectiveness of such technologies in enhancing students knowledge of scientific concepts and their desire to learn science through a mixed-method approach. A sample of 300 post primary students and 50 science teachers in urban and rural schools in Ireland were used to gather data. The results show that software technologies are of great help in increasing scientific literacy, especially with the help of pedagogical strategies that put emphasis on student-centered learning. Nevertheless, there are limitations related to such challenges as insufficient teacher training, a lack of access to technologies in rural environments, and inconsistency of policies that undermine the widespread distribution. The paper highlights the importance of thorough professional growth and equal distribution of resources to help to make the best out of technology in science education. The recommendations involve changes in the curriculum to incorporate the use of digital tools and special interventions to overcome infrastructural differences.